2018
DOI: 10.20964/2018.06.62
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Machining Multiple Slots of Bipolar Plates with Tool Vibration

Abstract: A bipolar plate is an important component of proton exchange membrane fuel cells (PEMFC). The fabrication of multiple slots is a key part in preparation of metallic bipolar plates. They can be produced by electrochemical machining (ECM). During the ECM process, high flow resistance occurs with the increase of slots length and depth, which will make metal hydroxide and other by-products accumulate in the outlet of electrolyte and limit the maximum feed rate of cathode. Therefore, a flow channels contraction cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…The results showed that multiple independent machining areas could effectively improve the speed uniformity of each channel. Jiang et al [23] proposed a variable cross-section channel contraction cathode structure. The flow rate of the electrolyte in the electrode gap gradually increased to better remove the electrolytic products.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that multiple independent machining areas could effectively improve the speed uniformity of each channel. Jiang et al [23] proposed a variable cross-section channel contraction cathode structure. The flow rate of the electrolyte in the electrode gap gradually increased to better remove the electrolytic products.…”
Section: Introductionmentioning
confidence: 99%